Pengaruh Risiko Audit Dan Risiko Bisnis Klien Terhadap Keputusan Penerimaan Klien Pada Kantor Akuntan Publik Di Jakarta: Client Business Risk, Audit Risk, Auditor Business Risk, Acceptance Decision Client - Rajagukguk, Thetty Surienty (Jurnal Ilmiah Raflesia Akuntansi, 2023)
Abstract-This study intends to examine the effect of client business risk, audit risk, and auditor business risk partially and simultaneously on client acceptance decisions at public accounting firms. This study used primary data obtained using questionnaires as data collection instruments. Each partner or manager represents the public accounting firm where he works to fill out a questionnaire. The population in this study is a public accounting firm in Jakarta. The sample used in this study was saturated sampling. Data analysis using multiple linear regression analysis. The test results show that the client's business risk does not have a significant effect on the client's onboarding decision. Meanwhile, the auditor's business risk negatively affects the client's onboarding decision. The higher the auditor's business risk, the lower the level of client onboarding decisions. Keywords: Client Business Risk, Audit Risk, Auditor Business Risk, Acceptance Decision Client